Identifikasi Hambatan Penerapan Lean di Usaha Kecil dan Menengah (UKM) - Mochammad Rifky Pamungkas; Erna Maulina; Margo Purnomo (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2021)
Today's world competition has increased the pressure on Small and Medium Enterprises (SMEs) to adopt lean implementations. The purpose of this study is to make a small contribution by exploring the Lean Implementation Barrier (LIB) in SMEs through three case studies of SMEs in the city of Bandung. A case study approach is used and followed by the Interpretative Structural Model (ISM) in order to see the inter-LIB relationship. The results of this study indicate that lack of management commitment and leadership, lack of employee involvement and lack of resources are the main obstacles to lean implementation in SMEs in Indonesia. Moreover, poor communication among various levels within the company and inadequate dissemination of knowledge about the benefits of lean also create barriers to lean implementation. The implication of this research is to strengthen and expand information related to research on the application of lean in SMEs, especially the results of the identified barriers that can assist SMEs in implementing lean or future research in developing and identifying barriers to implementing lean in SMEs.